Answer:
The expression is 2k + 4.
Step-by-step explanation:
You have to collect like-terms :
(8k + 9) - (6k + 5)
= 8k + 9 - 6k - 5
= 2k + 4
Hello,
f(x)=4(x+3)-5=4x+12-5=4x+7
y=4x+7==>c=(y-7)/4
f^(-1)(x)=(x-7)/4
f^(-1)( 3)=(3-7)/4=-4/4=-1
Answer D
I actually think its b cause it can't be d (thats obvious) yh........but i might be wrong
Answer:
900.
Step-by-step explanation:
The first 6 square numbers are 1, 4, 9, 16, 25, 36,
The required product is 25 * 36
= 900.
Here’s the correct answer and how I got it :)